Cannabidiol Is a Novel Modulator of Bacterial Membrane Vesicles - Kosgodage, Uchini S.; Matewele, Paul; Awamaria, Brigitte; Kraev, Igor; Warde, Purva; Mastroianni, Giulia; Nunn, Alistair V.; Guy, Geoffrey W.; Bell, Jimmy D.; Inal, Jameel M.; Lange, Sigrun (Frontiers in Cellular and Infection Microbiology, 2019)
Membrane vesicles (MVs) released from bacteria participate in cell communication and host-pathogen interactions. Roles for MVs in antibiotic resistance are gaining increased attention and in this study we investigated if known anti-bacterial effects of cannabidiol (CBD), a phytocannabinoid from Cannabis sativa, could be in part attributed to effects on bacterial MV profile and MV release. We found that CBD is a strong inhibitor of MV release from Gram-negative bacteria (E. coli VCS257), while inhibitory effect on MV release from Gram-positive bacteria (S. aureus subsp. aureus Rosenbach) was negligible. When used in combination with selected antibiotics, CBD significantly increased the bactericidal action of several antibiotics in the Gram-negative bacteria. In addition, CBD increased antibiotic effects of kanamycin in the Gram-positive bacteria, without affecting MV release. CBD furthermore changed protein profiles of MVs released from E. coli after 1 h CBD treatment. Our findings indicate that CBD may pose as a putative adjuvant agent for tailored co-application with selected antibiotics, depending on bacterial species, to increase antibiotic activity, including via MV inhibition, and help reduce antibiotic resistance.